Basketball referee 101 : 101 tips to start, grow and succeed as a basketball official from A to Z - Michaluk, Steven ([Fort Myers, Florida] : HowExpert, 2019)
If you want to learn the ins and outs of being a successful referee, start here! Having a mentor and bringing home an extra pay check aren$1 (Bt the only things you need to know. Use these tips to help you start your journey to success.s
Recommended Resources -- Publisher's Foreword -- Why would you officiate basketball -- Chapter 1. The Official guide to getting started as a referee -- Chapter 2. Bring Home the (extra) Bacon as a basketball referee! -- Chapter 3. Working better basketball games and seeing your schedule grow -- Chapter 4. Paying your dues (figuratively) -- Chapter 5. Settle down big timer! You're not refereeing on TV yet! -- Chapter 6. No one ever said officiating was easy -- Chapter 7. It's All about the journey -- About the expert -- Recommended resources.
Includes bibliographical references.
Keywords: BASKETBALL